Penerapan Evolution Strategies untuk Optimasi Travelling Salesman Problem With Time Windows pada Sistem Rekomendasi Wisata Malang Raya - Cahya Chaqiqi; Agus Wahyu Widodo; Yuita Arum Sari (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Tourism has became one of influential sectors that plays significant role in shaping the economy of a nation. Malang Raya is one of the place in Indonesia that have an abundance of tourism potential. Malang Raya is a region consisting of three different area of administration which are Kabupaten Malang, Kota Malang, and Kota Batu. Malang Raya has a large collection of destinations and attractions for tourists. On the other hand, the diverse tourism spots to visit can rise another issue as tourists left confused in choosing the best sites and destination alternatives that suit their expectations. The selection of routes faced with limited travel time is a common optimization problem known as Travelling Salesman Problem With Time Windows (TSP-TW). Optimization problem such of TSP-TW can be solved by utilizing Evolution Strategies (ES). According to the result acquired in (pre-research) assessment, the highest fitness value of 0,0041 is reached when the sum of population is 100 and the sum of generation is 15. The results of the optimization test obtained that the application can optimize the recommendation of respondents by 5.57%.